Simple, sensitive and specific detection method for polystyrene nanoplastics in food matrix based on peptide-modified Fe3O4@Au magnetic nanoparticles - Beibei Wang; Ling Sun; Kai Liu; Di Wu; Jinqiu Wang; Fang Geng (Current Research in Food Science)
Microplastics (MPs) and nanoplastics (NPs) are emerging hazardous pollutants that pose a significant threat to the global environment and human health. MPs and NPs have been detected in water sources and food products. Due to the wide variety of NPs, and low concentrations in environment and food samples, the rapid and selective detection of NPs still remains a challenge. Here, we prepared the peptide modified Fe3O4@Au magnetic nanoparticles as a selective probe to establish a simple, sensitive and specific method for polystyrene (PS) NPs detection. First, a layer of gold shell was in-situ grown on the surface of Fe3O4 to provide more modification sites, and the PS binding peptide (PSBP) was then modified by Au-S bonds to construct a selective probe for PS NPs. Under optimized detection conditions, ultra-low concentration of PS could be quantitatively detected by simply monitoring the UV–vis absorption change of the probe. The peptide modified Fe3O4@Au probe (Fe3O4@Au-PSBP) showed excellent linearity in the range from 0 to 80 pg mL−1 with the limit of detection (LOD) of 0.074 pg mL−1. The method has been successfully applied in real samples, such as bottled water, salt and milk with the recoveries from 89.15 % to 110.91 %. The proposed Fe3O4@Au-PSBP is easily extendable to other types of NPs by simply replacing the peptide, showing great potential as a universal specific probe for sensitive and rapid detection of low concentration NPs in the actual samples.